INTERNAL PUBLIC RELATION DAN MOTIVASI KERJA KARYAWAN PADA PT.ASTRA INTERNATIONAL TBK-HONDA SALES OFFICE MAKASSAR - Arief Sirajuddin; Hasniati Hasniati (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2019)
The purpose of this study was to determine the effect of internal public relations activities on employee motivation at PT. Astra International Tbk-Honda Makassar Sales Office Pupulation and the sample used were 82 respondents, while the analysis unit was employees of PT. Astra International Tbk-Honda Makassar Sales Office. While the analysis tool is simple linear regression analysis. The results of the analysis to determine the size of the contribution or contribution of internal public relations activities to employee motivation, then use the number R square or the Coefficient of Determination (KP). The amount of the R square is 0.884 or 88.4% of the influence of internal public relations activities on employee motivation. While the remaining 11.6% (100% -88.4%) is explained or caused by other factors outside the variable internal public relations activity.